2011
DOI: 10.1063/1.3665950
|View full text |Cite
|
Sign up to set email alerts
|

Copropagating pump and probe experiments on Si-nc in SiO2 rib waveguides doped with Er: The optical role of non-emitting ions

Abstract: We present a study that demonstrates the limits for achieving net optical gain in an optimized waveguide where Si nanoclusters in SiO 2 codoped with Er 3þ are the active material. By cross correlating absorption losses measurements with copropagant pump (k pump ¼ 1.48 lm) and probe (k probe ¼ 1.54 lm) experiments we reveal that the role of more than 80% of the total Er 3þ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Further increases in erbium concentration, such as in heavy doping, lead to a nonuniform distribution and erbium ions clustering 39 . Experimental results indicated that this increased concentration significantly reduced the population of optically active erbium ions 40 , complicating the realization of an adequate gain in waveguides within sub-millimeter length scales. Therefore, no net optical gain in the Er-doped Si-rich materials has yet been reported under electrical pumping.…”
Section: Er-related Light Sourcementioning
confidence: 99%
“…Further increases in erbium concentration, such as in heavy doping, lead to a nonuniform distribution and erbium ions clustering 39 . Experimental results indicated that this increased concentration significantly reduced the population of optically active erbium ions 40 , complicating the realization of an adequate gain in waveguides within sub-millimeter length scales. Therefore, no net optical gain in the Er-doped Si-rich materials has yet been reported under electrical pumping.…”
Section: Er-related Light Sourcementioning
confidence: 99%
“…Recently, we have demonstrated that this is followed by the loss of light emission capability of Er 3+ when embedded in SRO material [11]. While the main fraction of embedded erbium ions does not participate in the process of light emission, absorption properties of non-emitting ions remain unaltered [12]. Evidently, this becomes a major obstacle toward population inversion in this material.…”
Section: Introductionmentioning
confidence: 99%
“…In case For Er 3+ doped waveguide, above a threshold pump power of 1550 mW.mm -2 , a positive gross gain is reached which increases up to 2 dB.cm -1 for the highest pump power density simulated. In order to estimate the net gain, we must account for the background losses such as those found experimentally by Navarro-Urrios et al 25 They found on comparable waveguide losses of about 3 dB.cm -1 at 1532 nm, making it impossible to reach a positive net gain in this range of pump power density. In case of Nd 3+ doped waveguide, we find that the optical gain remains positive over the whole power range and it increases up to 30 dB.cm -1 for the highest pump power of 10 4 mW.mm -2 .…”
Section: Resultsmentioning
confidence: 99%